[RETRACTED ARTICLE] Alternative Relations Between Nature and Human Rights: decoloniality and the inter-american court of human rights case law - Lima, Felipe Costa; Acerbi, Vitória dos Santos; Correa, Igo Zany Nunes (Cadernos Eletrônicos Direito Internacional sem Fronteiras, 2022)
The editorial team of Cadernos Eletrônicos Direito Internacional sem Fronteiras - CEDIsF proceeded to retract the research due to the non compliance with the editorial norms (on March 22, 2023). The material was received on January 31, 2022, and the preliminary decision to publish was given on May 10, 2022; and was published on June 29, 2022.